2010
DOI: 10.2478/v10145-010-0012-9
|View full text |Cite
|
Sign up to set email alerts
|

Modification of Wood Pellets and Propane Co-firing in a Magnetic Field

Abstract: -When burning fossil fuels and renewable energy resources, greenhouse emissions (GHG) are emitted into the atmosphere. One of the options to reduce GHG emissions is to apply a magnetic field. The effect of a gradient magnetic field on the gasification of renewable fuel and the combustion of volatiles by applying the field to the bottom part of the swirl flame with recirculation is studied for the conditions of field-enhanced reverse heat and mass transfer of paramagnetic flame species up to the layer of wood p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…One of the options to control the process of the combustion characteristics is the application of external forces (electrical, magnetic) to the flame reaction zone. The previous experimental study has shown [4] and [5] that application of the external forces allows control of the flame formation of the flame velocity, temperature and composition profiles, determining the flame shape and structure, but interpretation of the mechanism of the field effects on the flame dynamics requires further detailed analysis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the options to control the process of the combustion characteristics is the application of external forces (electrical, magnetic) to the flame reaction zone. The previous experimental study has shown [4] and [5] that application of the external forces allows control of the flame formation of the flame velocity, temperature and composition profiles, determining the flame shape and structure, but interpretation of the mechanism of the field effects on the flame dynamics requires further detailed analysis.…”
Section: Introductionmentioning
confidence: 99%
“…Over the past twenty years, researchers from Japan have found that the magnetic field can cause significant changes in diffusion flame behaviour, such as changes in emissions from the flames, changes in flame shape and size and the extinction points [6], [7] and [8]. The complex experimental research of the magnetic field effects on the swirling flame flow dynamics during biomass combustion that is carried out in the Institute of Physics, University of Latvia [4] and [5] indicate that application of the gradient magnetic field to the bottom part of the flame reaction zone can be used to provide the enhanced mixing of the flame species with a radial expansion of the inner recirculation zone, increasing combustion efficiency and burnout of the volatiles.…”
Section: Introductionmentioning
confidence: 99%